Quantum analogue of Trapezoid-type inequalities for q-differentiable coordinated strongly convex functions - Mishra, Shashi Kant; Sharma, Ravina; Bisht, Jaya (Journal of applied mathematics & computing, 2025)
In this paper, with the help of quantum integrals and derivatives, we derive some q-Trapezoid-type inequalities for quantum differentiable coordinated strongly convex functions on bidimensional intervals and obtain new bounds using the q-Ho¨lder and power mean inequalities. We show that the results established in this paper generalize earlier findings. Additionally, we demonstrate our findings with the help of some examples. These developments not only reinforce the core tenets of convex analysis but also expand the applicability of Hermite-Hadamard-type inequalities to generalized convex functions on coordinates and provide valuable tools for data analysis and optimization problem-solving.